2023
DOI: 10.1111/famp.12853
|View full text |Cite
|
Sign up to set email alerts
|

“I miss not being able to offer my couples a box of tissues…”: Couples' and therapists' perspectives on the therapeutic alliance with the transition to online couple therapy

Abstract: The purpose of this study is to advance theory concerning the experiences of couples and therapists involved in online couple therapy and the meanings they assign to them, with a particular focus on the therapeutic alliance. Using constructivist grounded theory methodology, in‐depth semi‐structured online interviews were conducted with 36 individuals, including 18 couples who had participated in online couple therapy via videoconference. Additionally, 15 couple and family therapists were interviewed in four on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Since then, teletherapy has become part of standard practice for many clinicians ( Van Daele et al, 2020 ; Sheperis and Smith, 2021 ; Kwok et al, 2022 ), and a vast amount of research has suggested comparable efficacy with in-person treatment (e.g., Lin et al, 2022 ). Lots has been written about therapists’ experiences of the therapeutic process in teletherapy during the pandemic ( Békés et al, 2020 ; Perry et al, 2020 ; Rosen et al, 2020 ; Van Daele et al, 2020 ; Hanley and Wyatt, 2021 ; Helps and Le Coyte Grinney, 2021 ; Nuttman-Shwartz and Shaul, 2021 ; Poletti et al, 2021 ; Machluf et al, 2022 ; Stukenberg et al, 2022 ; Aviram and Nadan, 2023 ). These studies showed that overall, therapists had a reasonably favorable experience, often better than they expected, and their attitudes toward teletherapy became more positive ( Békés et al, 2020 ; Humer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, teletherapy has become part of standard practice for many clinicians ( Van Daele et al, 2020 ; Sheperis and Smith, 2021 ; Kwok et al, 2022 ), and a vast amount of research has suggested comparable efficacy with in-person treatment (e.g., Lin et al, 2022 ). Lots has been written about therapists’ experiences of the therapeutic process in teletherapy during the pandemic ( Békés et al, 2020 ; Perry et al, 2020 ; Rosen et al, 2020 ; Van Daele et al, 2020 ; Hanley and Wyatt, 2021 ; Helps and Le Coyte Grinney, 2021 ; Nuttman-Shwartz and Shaul, 2021 ; Poletti et al, 2021 ; Machluf et al, 2022 ; Stukenberg et al, 2022 ; Aviram and Nadan, 2023 ). These studies showed that overall, therapists had a reasonably favorable experience, often better than they expected, and their attitudes toward teletherapy became more positive ( Békés et al, 2020 ; Humer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These ndings contribute to the literature in several important areas. First, while therapists reported broad bene ts of telemental health services, they acknowledged telehealth involved communication limitations.The tendency to feel less personable over video calls has been a common nding in post-pandemic telehealth(Aviram & Nadan, 2023;Connolly et al, 2022;Cowan et al, 2019), and may have negative impacts upon therapeutic relationships (Aafjes-Van Doorn et al, 2023). Therapists in this study were enthusiastic about the potential to engage clients with VR technologies to build stronger therapeutic alliances.…”
mentioning
confidence: 99%